Polymer electrolyte fuel cells using nafion-based composite membranes with functionalized carbon nanotubes - Kannan, Ramaiyan; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2008)
Keywords: fuel cells; membranes; nanotubes; Polymers; proton transport

Preparation and characterization of rhodium nanostructures through the evolution of microgalvanic cells and their enhanced electrocatalytic activity for formaldehyde oxidation - Sathe, Bhaskar R.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2009)
Shape-controlled morphological evolution of nanostructured Rh has been demonstrated with the help of a galvanic displacement reaction using Al in 1 mM aqueous Rh(III) chloride at an open circuit potential 0.99 V and at a temperature of 273 K (room temperature). Nanospheres composed of small nanoparticles of size around 2.9 +/- 0.4 nm having uniform distribution with a FCC pattern have been evolved during the course of the reaction. Electrochemical results coupled with structural and morphological characterization data from transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and cyclic voltammetry (CV) suggested the formation of Rh nanostructures. Considering the role of the potential of substrate Al and Rh and diffusion of reactant and product species toward and from the surface of the Al, we proposed the tentative mechanism for the formation of microgalvanic cell. Significantly, these: rhodium nanostructures exhibit enhanced electrocatalytic activity toward many fuel cell reactions as demonstrated by formaldehyde oxidation in 0.5 M NaOH. The present strategy is expected to be valid for preparing many other similar electrocatalysts (Pt, Au, and Pd) capable of exhibiting such a remarkable size- and shape-dependent reactivity.